First-trimester vaginal bleeding: clinical presentation, associated factors, and pregnancy outcomes in a tertiary care setting - Patel, Rameshbhai C.; Chaudhari, Nimisha Jesangbhai; Patel, Mukundbhai B.; Shah, Ishan P. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Vaginal bleeding in the first trimester is a common occurrence, causing significant anxiety for patients and diagnostic challenges for clinicians. It is associated with a spectrum of outcomes, from viable pregnancies to pregnancy loss. Understanding the factors influencing these outcomes is crucial for patient counselling and management. Objectives were to evaluate first-trimester bleeding associated with miscarriage, ectopic pregnancy, and hydatidiform mole, and to assess the management and outcomes of pregnancies complicated by first-trimester vaginal bleeding. Methods: A prospective observational study was conducted on 200 women presenting with first-trimester vaginal bleeding at a tertiary health center in North Gujarat from September 2022 to February 2025. Data were collected through detailed history, clinical examination, and ultrasound findings. Patients were followed up to determine pregnancy outcomes. Bleeding severity was categorized as spotting, moderate, or heavy. Results: The majority of patients (72.5%) were in the 21-30 years age group. Primigravidas constituted 55% of cases. 70% of miscarriage cases were un-booked. A history of previous miscarriage was present in 40% of patients. Most presentations (35.5%) occurred at 8-10 weeks of gestation. Absence of abdominal pain was associated with a better outcome (44% viable versus 16% non-viable) compared to its presence (19% viable versus 21% non-viable). Spotting was associated with a high viability rate (85.8%), whereas all cases (100%) with heavy bleeding resulted in non-viable outcomes. Miscarriages were the most common diagnosis (90%). Overall, 63% were diagnosed as threatened miscarriages and managed conservatively. Subchorionic hematoma (SCH) was noted in 15 threatened miscarriage cases, with 40% having a favorable full-term outcome. Ultimately, 104 (52%) pregnancies had a viable outcome, while 96 (48%) were non-viable. Conclusions: First-trimester vaginal bleeding is strongly associated with adverse pregnancy outcomes, with the amount of bleeding and presence of abdominal pain being significant prognostic indicators. Spotting often has a favorable outcome, while heavy bleeding invariably leads to pregnancy loss. SCH negatively impacts prognosis. Timely evaluation, appropriate counselling, and management are essential to mitigate anxiety and improve maternal and perinatal outcomes.